Room‐Temperature Multi‐Beam, Multi‐Wavelength Bound States in the Continuum Laser. Issue 19 (18th July 2022) - Ha, Son Tung; Paniagua‐Domínguez, Ramón; Kuznetsov, Arseniy I.
Abstract: A highly polarized multi‐beam, multi‐wavelength III–V semiconductor laser based on the concept of bound states in the continuum (BIC) is reported. By utilizing destructive interferences of guided‐mode resonances in an active slab supported by a grating structure, both symmetry‐protected and accidental BIC resonances are created within the gain spectrum of InGaP multi‐quantum wells and achieve lasing in these modes simultaneously. Well‐defined multi‐lasing beams at different wavelengths (i.e., 664.9 nm @ 0.2°, 656.4 nm @ 2.5°, 646.4 nm @ 5.1°, and 636.7 nm @ 7.6°) with transverse magnetic polarization can be obtained in a single device operating at room temperature. Furthermore, the lasing wavelengths can be precisely tuned by changing the grating parameters. The laser concept presented in this paper is promising for applications in highly directional surface‐emitting lasers, optical communications, bio‐sensing, and signal processing. Abstract : Simultaneous excitation of symmetry‐protected and accidental Bound States in the Continuum in an AlGaP quantum well slab coupled to a grating enables a highly polarized multi‐beam, multi‐wavelength laser. The lasing wavelengths can be precisely tuned by changing the grating parameters paving the way for applications in highly directional surface‐emitting lasers, optical communications, bio‐sensing, and signal processing.